Elevating Employee Performance: The Mediating Role of Job Satisfaction in Batam's Four-Star Hotels: Meningkatkan Kinerja Karyawan: Peran Mediasi dari Kepuasan Kerja di Hotel Bintang Empat di Batam - Lilis; Yuddy Giovanna Priscilla (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
The research was designed to analyze how training, compensation, work environment, and motivation affect employee job satisfaction and performance, with a particular focus on understanding both direct and indirect effects. The object of this study is a four-star hotel in Batam City, and the sample consisted of 320 respondents. Data were collected through questionnaires, and the analysis was conducted using the Smart PLS application. The results of the study indicate that compensation significantly influences employee job satisfaction and performance, while training, work environment, and motivation also play crucial roles in enhancing overall employee effectiveness.